Why some are more equal: Family firm heterogeneity and the effect on management's attention to CSR. (4th February 2019) - Fehre, Kerstin; Weber, Florian
Abstract: Research at the family firm–Corporate Social Responsibility (CSR) nexus lacks agreement about whether family firms are more or less socially responsible than their non‐family counterparts, which leads discussion relating to the bright and dark side of socioemotional wealth (SEW). We add to this ongoing debate in two different ways. First, we build on family firm heterogeneity and argue for a gray side to SEW, located between the bright and dark sides that is dependent upon the kind of family firm ownership. Second, we assume that prior research on a diverse set of CSR behaviors may, to some extent, explain the contradicting results; thus, we propose going back a step and focusing on management's attention to CSR as an important antecedent of CSR behavior. By analyzing the letters to the shareholders of German HDAX firms from 2003 to 2012, this study finds that family ownership positively affects management's attention to CSR, mainly driven by founders and family foundations. The research adds to our understanding of the family firm–CSR nexus by scrutinizing the role SEW plays in management's attention to CSR when it comes to family firm heterogeneity.